Appraisal of Nigeria's Ceramic Tile Production - Abiola, Oluranti (Journal of Engineering Science and Technology Management (JES-TM), 2023)
Ceramic tiles are made from clay materials and are mostly fired at very high temperatures. Despite the local availability and accessibility of the materials in abundance in Nigeria, only 11% of ceramic tiles consumed in the country are produced locally and imported raw materials are employed to achieve this. Hence, this work tends to provide quality data on the availability of ceramic raw materials and their locations within the country. Studies on the production of ceramic tiles from materials collected locally were considered in this paper. This current work highlighted the various categories of ceramic products and focused on the availability and feasibility of clay materials collected from Nigeria for ceramic tiles production. It also looked at Nigeria’s ceramic tiles industry and Nigeria’s placement among the nations of the world in ceramic tiles manufacturing and consumption. This review offers an evaluation of the studies carried out on the production of ceramic tiles for covering walls and floors in residential and non-residential buildings.